Letters from the Havana, During the Year 1820 Containing an Account of the Present State of the Island of Cuba, and Observations on the Slave Trade - Jameson, Robert Francis (Cambridge library collection. Slavery and Abolition, 1821)
Robert Francis Jameson was the British Commissioner of Arbitration stationed in Cuba between 1819 and 1823. This volume, first published in 1821, contains his observations of Cuba, recorded during his year-long stay in Havana in 1820. Jameson provides a comprehensive description of Cuban society and a detailed account of the city of Havana, illustrating the stark differences between the classes in Havana society. At this time, Cuba was the world's leading producer of sugar cane, and totally dependent on slave labour and the slave trade. Jameson discusses the impact of slavery on the Cuban economy and the advantages and disadvantages of emancipation. He also discusses Cuba's constitutional history and contemporary economy, exploring the effects of Ferdinand VII's opening of Havana to foreign trade. Written in the form of letters to an anonymous recipient, this volume provides a valuable and fascinating picture of contemporary Cuban society